Prevalence of Hepatozoon spp. (Apicomplexa, Hepatozoidae) among recently captured Brazilian snakes - O'Dwyer, L.H. [UNESP]; Moço, T.C. [UNESP]; Barrella, T.H. [UNESP]; Vilela, F.C. [UNESP]; Silva, R.J. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2003)
O presente estudo teve como objetivo determinar a prevalência da infecção por Hepatozoon spp. em serpentes recém-capturadas da região de Botucatu, São Paulo. O sangue foi coletado de todas as serpentes por punção da veia caudal. Os esfregaços foram secos ao ar, fixados com metanol e corados com solução de Giemsa a 10%. Examinaram-se 238 serpentes pertencentes a 23 espécies, das quais 135 (56,7%) eram venenosas e 103 (43,3%) não venenosas. As espécies venenosas mais representativas foram Crotalus durissus terrificus (n=108) e Bothrops jararaca (n=17) e as não venenosas foram Oxyrhopus guibei (n=35), Boa constrictor amarali (n=18) e Waglerophis merremi (n=13). A infecção por Hepatozoon spp. foi detectada em 39 (16,4%) serpentes. As prevalências em serpentes venenosas e não venenosas foram 20,0% e 11,7%, respectivamente. As maiores prevalências foram 38,9% para Boa constrictor amarali, 35,3% para Bothrops jararaca e 19,4% para Crotalus durissus terrificus.

The goal of this study was to determine the prevalence of Hepatozoon spp. infection in recently captured snakes from Botucatu, São Paulo State, Brazil. Blood was collected from all snakes by ventral tail venipuncture. Blood smears were air dried, fixed with methanol, and stained with 10% Giemsa solution. The slides were microscopically examined for detection of hemoparasites by light microscopy at 250x magnification. A total of 238 snakes from 23 species were examined, of which 135 (56.7%) were venomous and 103 (43.3%) non-venomous snakes. The more numerous venomous species sampled were Crotalus durissus terrificus (n=108) and Bothrops jararaca (n=17) and non-venomous snakes were Oxyrhopus guibei (n=35), Boa constrictor amarali (n=18), and Waglerophis merremi (n=13). Hepatozoon spp. infection was detected in 39 (16.4%) snakes. The prevalence in venomous and non-venomous snakes was 20.0% and 11.7%, respectively. The highest prevalences observed were 38.9% for Boa constrictor amarali, 35.3% for Bothrops jararaca, and 19.4% for Crotalus durissus terrificus.
Prevalência de Hepatozoon spp. (Apicomplexa, Hepatozoidae) em serpentes recém-capturadas no Brasil
Keywords: serpente; Hepatozoon; prevalência; infecção; snake; Hepatozoon; prevalence; infection